Multilateral activity model: improving children's gross motor - Anggi Setia Lengkana (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Gross motor development of children is very important for their physical and cognitive growth. However, many children face difficulties in this regard. Multilateral activity models involving various body movements can be effective in stimulating and improving gross motor skills in early childhood.